Optical Absorption and Electron Injection of 4-(Cyanomethyl)benzoic Acid Based Dyes: A DFT Study - Yuehua Zhang; Penghui Ren; Yuanzuo Li; Runzhou Su; Meiyu Zhao (Journal of Chemistry)
Density functional theory (DFT) and time-dependent density functional theory (TDDFT) calculations were carried out to study the ground state geometries, electronic structures, and absorption spectra of 4-(cyanomethyl)benzoic acid based dyes (AG1 and AG2) used for dye-sensitized solar cells (DSSCs). The excited states properties and the thermodynamical parameters of electron injection were studied. The results showed that (a) two dyes have uncoplanar structures along the donor unit and conjugated bridge space, (b) two sensitizers exhibited intense absorption in the UV-Vis region, and (c) the excited state oxidation potential was higher than the conduction band edge of TiO2 photoanode. As a result, a solar cell based on the 4-(cyanomethyl)benzoic acid based dyes exhibited well photovoltaic performance. Furthermore, nine dyes were designed on the basis of AG1 and AG2 to improve optical response and electron injection.